The Effect of Concealed Handgun Carry Deregulation in Arizona on Crime in Tucson. (October 2019) - Smith, Michael R.; Petrocelli, Matthew
In 2010, the Arizona legislature effectively deregulated concealed handgun carry in the state by passing Senate Bill (SB) 1108, which eliminated licensing and training requirements for concealed carry. Although researchers have extensively examined the impact of state adoption of concealed carry laws, almost nothing is known about the effects of deregulating concealed carry altogether. This study contributes to the more guns, less crime debate by examining the impact of Arizona's decision to deregulate concealed carry. Using a multiple time-series research design with an experimental (Tucson) and control city (El Paso), the present study examines the impact of deregulation on handgun-related violent crime and gun larcenies in Arizona's second largest city—Tucson. We find that the passage of SB 1108 had no impact on handgun-related offenses that could be expected to change following deregulation. The implications of these findings for policy making and future research are discussed.